Mr. Private University Barriers to World-Class Education: The Case of Indonesia - Widiputera, Ferdi; Agung, Iskandar (Universitas Negeri Semarang, 2023)
This study provides a comprehensive analysis of the barriers that prevent private universities from achieving world-class status. Six private universities with national A, B, and C accreditations were examined using qualitative methods including interviews, focus groups, and university documents, as well as the Times Higher Education (THE) assessment criteria in 2021. The research highlights a stark contrast between private universities in developed countries, which have more flexibility in achieving World-Class University (WCU) status, and those in Indonesia, which face significant challenges. Obstacles include the youth of the institutions, limited student enrollment, faculty lacking doctoral degrees, inadequate adoption of international teaching methods, insufficient research output, and weak research linkages. There's also a lack of language skills among faculty, a shortage of international staff, and limited collaboration with recognized institutions. The paper recommends that private universities improve the quality of education with government support through incentives, funding for domestic and international doctoral training, modern research facilities, and other relevant initiatives.